A novel ultra-sensitive method for the detection of FGFR3 mutations in urine of bladder cancer patients - Design of the Urodiag® PCR kit for surveillance of patients with non-muscle-invasive bladder cancer (NMIBC) - Jean-Pierre Roperch; Claude Hennion (BMC, 2020)
Abstract Background We have recently developed a highly accurate urine-based test, named Urodiag®, associating FGFR3 mutation and DNA methylation assays for recurrence surveillance in patients with low-, intermediate-, and high-risk NMIBC. Previously, the detection of four FGFR3 mutations (G372C, R248C, S249C and Y375C) required amplification steps and PCR products were analyzed by capillary electrophoresis (Allele Specific-PCR, AS-PCR), which was expensive and time-consuming. Here, we present the development a novel ultra-sensitive multiplex PCR assay as called "Mutated Allele Specific Oligonucleotide-PCR (MASO-PCR)", generating a cost-effective, simple, fast and clinically applicable assay for the detection of FGFR3 mutations in voided urine. Methods Comparative clinical performances of MASO-PCR and AS-PCR technologies were performed from 263 urine DNA samples (87 FGFR3 mutated and 176 FGFR3 wild-type). In the development of Urodiag® PCR Kit, we studied the stability and reproducibility of each all-in-one PCR master mix (single reaction mixture including all the necessary PCR components) for MASO-PCR and QM-MSPCR (Quantitative Multiplex Methylation-Specific PCR to co-amplify SEPTIN9, HS3ST2 and SLIT2 methylated genes) assays. Results Complete concordance (100%) was observed between the MASO-PCR and AS-PCR results. Each PCR master mix displayed excellent reproducibility and stability after 12 months of storage at − 20 °C, with intra-assay standard deviations lower than 0.3 Ct and coefficient of variations (CV) lower than 1%. The limit of detection (LoD) of MASO-PCR was 5% mutant detection in a 95% of wild-type background. The limit of quantification (LoQ) of QM-MSPCR was 10 pg of bisulfite-converted DNA. Conclusions We developed and clinically validated the MASO-PCR assay, generating cost-effective, simple, fast and clinically applicable assay for the detection of FGFR3 mutations in urine. We also designed the Urodiag® PCR Kit, which includes the MASO-PCR and QM-MSPCR assays. Adapted to routine clinical laboratory (simplicity, accuracy), the kit will be a great help to urologists for recurrence surveillance in patients at low-, intermediate- and high-risk NMIBC. Reducing the number of unnecessary cystoscopies, it will have extremely beneficial effects for patients (painless) and for the healthcare systems (low cost).